From Bach–Busoni to Bach–Grainger: Adaptation as Composition. Issue 1 (2nd January 2017) - Knyt, Erinn
Abstract : Percy Grainger's nearly lifelong fascination with the music of J.S. Bach began when he encountered the Bach interpretations of Louis Pabst in Australia at the age of ten and then subsequently studied the Well-Tempered Clavier and other compositions by Bach with him. Yet it was after a few weeks of studying Bach–Busoni transcriptions with Ferruccio Busoni in Berlin during the summer of 1903 that the compositions of Bach took on greater aesthetic and poietic significance for him. Even despite the fact that the relationship eventually 'soured', discussions with Busoni in Berlin (and subsequently in London and the United States) reinforced some of Grainger's burgeoning countercultural aesthetic ideas, especially ones deriving from the music of Bach: scepticism about the concept of 'originality', an interest in flexible instrumentation, and an idealization of polyphony. Although several scholars have discussed the Busoni–Grainger relationship, its importance for Grainger's artistic ideals has yet to be explored in any degree of detail. Through analyses of scores, manuscripts, essays, concert programmes, recordings, and letters, including unpublished documents from the Grainger Museum at The University of Melbourne, this article presents the first detailed exploration of the ways Grainger's aesthetics, poietics, and interpretations were influenced by Busoni's vision of Bach. In so doing, the article lends greater insight into the development of Grainger's unique compositional style, and contributes to current discourse about the role and value of adaptations in the early twentieth century. In particular, it reveals that while participating in an early-twentieth-century fascination with the music of Bach, the ideas Busoni transmitted to Grainger held even wider ranging significance. They represent a move away from the modernist notion of progress into a proto-postmodernist mindset in which appropriation, reuse, adaptation, and reshaping hold as much value as the original and new.